2004
DOI: 10.1039/b307997j
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical α-cleavage of ketones: revisiting acetone

Abstract: The photochemical [small alpha]-cleavage of acetone is analyzed in view of recent results obtained for the isolated molecule in supersonic jets. The fluorescence decay time of the isolated molecule spans a range of more than six orders of magnitude, from approximately 10(-6) s near the origin of the S(0)-S(1) transition to less than 10(-12) s at about 20 kcal x mol(-1) excess energy. In contrast, the decay time of the excited singlet (S(1), (1)n pi) in the bulk is around 10(-9) s and independent of excitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 75 publications
(80 reference statements)
3
88
2
Order By: Relevance
“…Photolysis of acetone is one of the most extensively studied photochemical reactions [118]. The CC bond dissociation, called "Norrish type I reaction" (CH 3 ) 2 CO → CH 3 CO + CH 3 , has been the main focus of many theoretical and experimental studies [119][120][121][122][123][124][125][126][127][128][129][130][131][132][133].…”
Section: Photodissociation Of Acetonementioning
confidence: 99%
“…Photolysis of acetone is one of the most extensively studied photochemical reactions [118]. The CC bond dissociation, called "Norrish type I reaction" (CH 3 ) 2 CO → CH 3 CO + CH 3 , has been the main focus of many theoretical and experimental studies [119][120][121][122][123][124][125][126][127][128][129][130][131][132][133].…”
Section: Photodissociation Of Acetonementioning
confidence: 99%
“…Specifically it has been shown that, in the case of toluene as absorber, the signal contrast increases with total pressure whereas, in the case of acetone, the contrast decreases with increasing total pressure. This phenomenon has been explained qualitatively in terms of the model presented by Haas whereby the effective quench rate via rapid photodissociation of acetone following ISC for excitation above the triplet barrier is reduced by rapid, collision-induced internal relaxation to lower lying and longer-lived singlet and triplet states [17]. The present work has been restricted to excitation of toluene and acetone by radiation at 266 nm but future work could explore the variation in relative relaxation rates as a function of excitation energy relative to the lowest bound excited states of such hydrocarbons.…”
Section: Resultsmentioning
confidence: 98%
“…This is explained by the presence of a dissociative triplet state, with an associated barrier in the T 1 state approximately 94 kcal mol À1 above S 0 [17]. Dissociation via the triplet state results in rapid energy transfer to the bulk gas.…”
Section: Photophysics Of Toluene and Acetonementioning
confidence: 96%
See 1 more Smart Citation
“…In fact, by some accounts [35], the photolysis of acetone is one of the most studied of all gas-phase reactions. For excitation at a wavelength of 266 nm, the photoreaction proceeds by a Norrish Type I process in which the alpha carbon undergoes bond scission as follows:…”
Section: The Influence Of Photochemistry and Pyrolysis On Plume Dynamicsmentioning
confidence: 99%